CAFF Map No.57 - Location of datasets in the Arctic Species Trend Index - Arctic Council , Conservation of Arctic Flora and Fauna Working Group (CAFF International Secretariat, 2010)
CAFF Map No.57 - Location of datasets in the Arctic Species Trend Index, 2010